1970
DOI: 10.3126/kuset.v5i1.2850
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Solasodine from <i>in vitro</i> and <i>in vivo</i> Cultures of <i>Solanum nigrum</i> Linn.

Abstract: An efficient protocol was devised for rapid callus induction of Solanum nigrum Linn. from young leaves. MS medium supplemented with different concentrations IAA (1-3 mg/l) with BAP (0.5 mg/l) and NAA (1-3 mg/l) with BAP (0.5 mg/l) for callus initiation. The growth of the calli derived from leaves increased with time of incubation and remained almost constant after 30 days. For solasodine estimation, the field grown plant part of young leaves and in vitro callus (0.5 g each) were weighed and extracted thrice wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…These findings are in synchrony with those of Janarthanam et al [18] and Rajkumar et al [19], who have obtained large amount of bioactive compound in undifferentiated callus culture than field grown plants. Similar studies have been conducted in Solanum nigrum [20], wherein the authors have reported that the solasodine content from the in vitro callus extracts was much higher than extracts of field grown leaves.…”
mentioning
confidence: 55%
“…These findings are in synchrony with those of Janarthanam et al [18] and Rajkumar et al [19], who have obtained large amount of bioactive compound in undifferentiated callus culture than field grown plants. Similar studies have been conducted in Solanum nigrum [20], wherein the authors have reported that the solasodine content from the in vitro callus extracts was much higher than extracts of field grown leaves.…”
mentioning
confidence: 55%
“…Results of earlier experiments revealed that total glycoalkaloid content per dry weight was less than 0.2% in the roots when this plant was grown in natural conditions. Several papers have described the production of solasodine, a type of glycoalkaloid, in tissue cultures of Solanum laciniatum (Macek 1989) and Solanum nigrum (Yogananth et al 2009). However, glycoalkaloid production in cultured tissue of Solanum species has not received much attention, and there have been a limited number of reports relating to the tissue culturing of S. hainanense (Anh et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Berberine alkaloid was produced from in vitro culture of Thalictrum minor 1 000 folds than original plant [13]. In vitro production of solasodine from cultures of S. nigrum (0.142 mg/g) in higher yields than parent plant (0.079 8 mg/ g) which was equal to 1.78 folds was also reported [15]. High yield of glycoalkaloids of solanidine series from Solanum tuberosum culture, reached 1.44 and 3.88 folds of the concentration of mother plant from calli and shoots, respectively were reported from Solanum tuberosum cultures [16].…”
Section: Table 11mentioning
confidence: 92%
“…The challenge of producing natural antibilharziasis drugs from plant origin lead to searching for alternative way rather than breeding for producing such valuable compounds. Different studies of in vitro glycoalkaloids production from Solanum species are reported [13][14][15][16].…”
Section: A Rt I C L E I N F O Abstractmentioning
confidence: 99%